Gen Y’s attitude, perception, preference, and intention towards Private Label Brands (PLBs) - Sawanah Mumin; Phang Ing @ Grace (Sarawak Research Society, 2022)
The present paper focuses on Gen Y consumers’ perceptions and preferences towards private label brands (PLBs). Gen Y, also known as ‘echo boomers’ or the ‘millennium generation’, have different spending habits compared to other generational cohorts. Given that they are the largest consumer group in Malaysia, a closer examination of their attitudinal and conative structures pertaining to PLBs would contribute to a better understanding of these brands’ potential growth. Store- and PLB-related criteria (perceived risk and PLB image) and individual criteria (innovativeness and familiarity) were considered as factors that contribute to the formation of Gen Y consumers’ attitude structure. The relationship between attitude and intention was proposed to be moderated by individuals' self-congruity. Using the purposive sampling technique, 256 usable survey responses were generated from Gen Y consumers in Sabah. Analysis results confirmed that both store and individual characteristics such as perceived risk, PLB image, and familiarity with PLBs have significant relationships with the attitude towards purchasing PLBs, while consumer innovativeness did not appear to be a key consideration in forming PLB-related attitude. In turn, attitude towards PLBs was found to significantly affect purchase intention as well as to mediate the influences of perceived risk, PLB image, consumer innovativeness, and familiarity on purchase intention. The results also showed that individuals with a high level of self-congruity with PLBs have a stronger intention to purchase when their attitude is positive. The findings imply the possibility of enhancing target consumers’ intention to buy PLBs by reinforcing their attitude structure through the cultivation of their self-congruity with PLBs. This could be done by strengthening aspects related the store, the individual, and the PLB itself.